Green Cloud Computing for Environmental Sustainability - Chiranjeevulu, Tirumala (Digital Repository of Theses - SSBM Geneva, 2024)
Public and Private Cloud infrastructure is keep increasing considerably in datacenter electrical power consumption, which has become a serious issue. Datacenter energy use for cloud computing applications affects the environment and raises operating expenses. One major issue with the current trend of energy scarcity and climate change is the power consumption of datacenters. As a result, we need cloud computing solutions that respect the environment and use less energy. Elevated energy consumption leads to harmful carbon emissions and increased operating expenses, which reduce cloud providers' profit margins. Thus, energy saving solutions are very much needed to reduce cloud computing environmental effects. To improve such solutions, a comprehensive analysis of cloud computing's power efficiency is very much necessary. With quick improvement and inevitable utilization of web and information advancement, Information Security has gotten to be the leading most challenging issues for various organizations. Security specialists and pros have been endeavoring troublesome to secure the computers, information and centralized orchestrate system. These security threats increase more when information is held outside the interior computing environment. Besides, IT businesses are as of late pushed by environment control to decrease the CO2 impression of information development system, era and shapes lines. Concurring to afterward experiences IT industry is able of making 4 % of carbon impression through their immense utilization of imperativeness.